Vertrauen in grenzüberschreitenden Akteursnetzwerken. Erkenntnisse aus dem deutsch-polnisch-tschechischen Kooperationsprojekt ENLARGE-NET. - Klein-Hitpaß, Katrin; Leibenath, Markus; Knippschild, Robert (TH Zürich, NSL, 2006)
Die Bedeutung von Vertrauen als Element von Sozialkapital und als Basis von Netzwerken wird von zahlreichen Autoren betont. Ebenso gibt es diverse Untersuchungen zum Management regionaler Netzwerke. Bislang wurde jedoch kaum beachtet, wie der Vertrauensaufbau in Netzwerken gezielt gefördert werden kann und welche Besonderheiten bei grenzüberschreitenden Netzwerken zu beachten sind. Es wird der Frage nachgegangen, welche Faktoren für den Aufbau von Vertrauen in grenzüberschreitenden Netzwerken ausschlaggebend sind und wie diese durch ein gezieltes Netzwerkmanagement beeinflusst werden können. Hierzu wird eine Reihe hypothesenartiger Einflussgrößen abgeleitet und durch eine Fallstudie empirisch unterlegt. difu

As trust is essential for close co-operation, its crucial role for the functionality of networks has been increasingly acknowledged in recent years. Its role is even more important in transboundary networks due to a lack of the opportunity to impose sanctions, the asynchronicity of exchange, and the high importance of personal interactions. However, there is little said about the chances to foster the establishment of trust and the special conditions of building up trust in cross-border co-operation. To investigate these questions, an empirical study was carried out with the German, Polish and Czech actors of the EU funded co-operation project ENLARGE-NET. The findings revealed that joint experiences and repeated interactions, direct communication, cross-border institutions, social distance and the commitment of a third party are the most important factors influencing the development of trust among the parties involved. To strengthen the process of building-up trust among actors in transboundary co-operations, a "trust management" programme should be implemented that aims at high contact frequency to guarantee a professional as well as personal exchange, an exchange that in addition secures a direct communication of the participants despite differences in languages, imposes well-defined rules of behavior and competencies, and influences the composition of participants to narrow the social distance and establish a feeling of equality. However, building up trust is a long-term process that is not easily fostered and is very sensitive to disturbances, which can stop the process immediately. difu
Keywords: Regionalplanung; Kommunale Zusammenarbeit; Kooperation; Leitbild; Verwaltung; Fallstudie; Netzwerk; Internationale Zusammenarbeit; Grenzüberschreitend; Pilotprojekt; Vertrauensbildung